Fiber-Bragg-grating-based ultrathin shape sensors displaying single-channel sweeping for minimally invasive surgery - Moon, Hyowon; Jeong, Jinwoo; Kang, Sungchul; Kim, Keri; Song, Yong-Won; Kim, Jinseok (ELSEVIER SCI LTD, 2014)
We report on the development of a highly flexible, thin shape sensor that can be integrated into minimally invasive surgery systems. Three optical fibers are arranged in a triangular shape and epoxy molded to produce a sensor diameter of less than 900 mu m, ensuring high-bending operation up to 90 degrees. Each fiber contains four fiber Bragg gratings (FBGs) operating at different wavelengths. With simultaneous detection of all the grating signals, the overall curvatures and torsions are interpolated and used for three-dimensional shape reconstruction. Three FBGs located at the same axial location also enables temperature compensation. Real-time shape monitoring with a sampling rate of 3.74 Hz is realized. The average tip position error was 1.50% of the total sensor length. (C) 2014 Published by Elsevier Ltd.
Keywords: BEND MEASUREMENT; OPTICAL-FIBER